Trends in Seagrass Research and Conservation in Malaysian Waters: Seagrass research in Malaysia - Abdulla- Al-Asif; Abu Hena Mustafa Kamal; Mohd Hanafi Idris; Md Khurshid Alam Bhuiyan; AFM Arifur Rahman (Journal of Tropical Life Science, 2023)
The seagrass ecosystems found in the marine and coastal areas, with substantial economic and ecological services and span all over the globe excluding the Antarctic region. The Coral Triangle and Southeast Asia are recognized as a worldwide hotspot of seagrass species and habitats, encompassing 10-21 species of seagrass in every nation, although the study, understanding, and quantity of publications on seagrass ecosystems are rather limited in the region, including Malaysia. Malaysia contains 18 seagrass species from three families, which occupy 16.8 km2 of coastal area, where the study and discovery of seagrass species and meadows began in 1904 with the report of Beccari. All of the published papers reviewed reported on Malaysian seagrass-related research, which was divided into nine topic groups: biology and distribution, carbon sequestration, fauna, remote sensing, impact and pollution genetic study, restoration, microbiological investigation, and others. The extensive study of the seagrass ecosystem began in 1993, and we have identified 183 published papers from Scopus, 141 publications from Web of Science, and 42 from Google Scholar. However, the average trend of the number of publications from 1993 to 1999 was 0.71 ± 0.36, while from 2000 to 2022 was 7.70 ± 1.16 followed by the average trend of the yearly number of publications was 6.78 ± 1.08. The highest number of publications was found on faunal categories (43.17%), followed by biology and distribution (21.85%). The number of articles that were published on Malaysian seagrass meadows each year has been discovered to be rising, which indicates that the trends in seagrass study and publishing were progressively garnering the attention of researchers, academics, and the government. However, to better understand the sustainable ecology and ecosystem services provided by seagrass habitats, an emphasis on certain research niches, such as the genetic study of flora and fauna in seagrass meadows, microbial ecology, and restoration as well as conservation of seagrass species might be helpful.